Pengaruh Literasi Keuangan terhadap Nilai Konsumtif Mahasiswa Pendidikan Ekonomi 2022 - Irma Siagian; Saidun Hutasuhut; Dewi Larasati Sinaga; Fitry Ulinda Tinambunan; Sarah Lylia Saragi; Veranita Sitio; Yefoni Valentina Banjar (Departement of Mathematics Education, 2024)
This research aims to analyze the influence of financial literacy on the consumptive behavior of students in the Economic Education Study Program, Medan State University class of 2022. The research uses a correlational quantitative approach with survey methods. Data was collected through a Likert scale-based questionnaire that measures financial literacy and consumer behavior. The results show that financial literacy has a significant influence on student consumptive behavior with a coefficient of determination (R²) of 38.3%. Students with a higher level of financial literacy tend to be wiser in managing their finances, so they are able to suppress consumer behavior. This research emphasizes the importance of financial literacy education as an effort to increase students’ financial awareness to support their financial independence in the future.